The Silent Witnesses: Forensic Entomology in the estimation of time since death”- A cross-sectional study from a tertiary hospital mortuary in South India (Journal of Forensic Medicine & Toxicology, 2025)
Forensic entomology is the application of the biology of insects and their arthropod relatives that interact with humans,  human remains, and the associated physical environment, to aid in the investigation of crimes, deaths, and other legal  matters. Despite its importance, forensic entomology remains under-utilized because of its limited awareness and lack  of region-specific data. This study bridges this gap by exploring entomological evidence applications in forensic investigations within South India’s unique geo-climatic conditions. This cross-sectional study analyzed 153 autopsies of  decomposed dead bodies with entomological evidence conducted at a tertiary hospital mortuary in South India from  January 2021 to December 2021. This study demonstrates the application of forensic entomology in estimating the time  since death and highlights its potential in aiding forensic investigations. We used two distinct methods to estimate the  post-mortem interval: Analyzing successional waves of insects for bodies over a month old and focusing on maggot  developmental stages for corpses under a month old. A comparative analysis was conducted to assess the validity and  reliability of entomological analysis in estimating post-mortem interval. The study systematically compared post-mor tem interval estimates derived from entomological evidence with those obtained from other post-mortem changes, as  well as information provided in autopsy reports. Utilizing Pearson correlation heat map analysis, the results revealed a  significant positive correlation between entomological estimates and those derived from other post-mortem changes  and autopsy reports. The findings of this study confirm entomological analysis as a reliable, complementary method for  determining post-mortem interval, highlighting its forensic utility.
Keywords: Forensic entomology; Time since death; Post-mortem interval; Maggots